Substance P ameliorates tumor necrosis factor‐alpha‐induced endothelial cell dysfunction by regulating eNOS expression in vitro. (11th April 2018) - Piao, Jiyuan; Hong, Hyun Sook; Son, Youngsook
Abstract: Objective: The aim of this study was to explore the beneficial effects of SP on NO production and inflammation‐induced vascular endothelium cell death. Methods: To mimic the inflammatory environment, TNF‐α was treated with HUVECs, and SP was added prior to TNF‐α to determine its protective effect. WST‐1 assay was performed to detect cell viability. NO level in conditioned medium was measured by Griess Reagent System. The protein level of cleaved caspase‐3, eNOS, and phosphorylated Akt was detected by Western blot analysis. Results: TNF‐α declined endothelial cell viability by downregulating Akt and NO production. TNF‐α‐induced cell death was reliably restored by NO, confirming the requirement of NO for cell survival. By contrast, pretreatment of SP attenuated TNF‐α‐induced cellular apoptosis, accompanied by an increase in the phosphorylation of Akt, eNOS expression, and NO production. Blockage of NK‐1R, phosphorylated Akt or eNOS by CP‐96345, A6730, or L‐NAME entirely eliminated the effect of SP. Conclusions: SP can protect the vascular endothelium against inflammation‐induced damage through modulation of the Akt/eNOS/NO signaling pathway.